Default Option, Risk-Aversion and Household Borrowing Behaviour - Ingrid Groessl; Ulrich Fritsche (Hamburg University, Department Economics and Politics, 2007)
Assuming a risk-neutral bank and assuming household utility to be exponential, we show how under information symmetry the covariance of income and loan repayments may explain higher household borrowings than in the case without default option. Under ex post information asymmetry and positive control costs, the result is less clear-cut. We also make evident that in a situation in which a household without default option would neither borrow nor save, the existence of a default option makes household borrowing behaviour unpredictable.
Keywords: D11; D14; D18; D53; D81; 330; Consumption; exponential utility; certainty equivalent; households; default option; borrowing; risk; risk aversion; risk management